Pelatihan Peningkatan Kompetensi Kewirausahaan Bagi Guru SD Kab. Mimika - Syamsuddin, Afdhal Fatawuri; Rahman, Abdul; Pagarra, Hamzah; Rahman, Hardianto; Atjo, Syamsuriani Eka Putri (Universitas Negeri Makassar, 2025)
This community service program aimed to enhance entrepreneurship competencies among elementary school teachers in Mimika Regency, Papua. Through participatory workshops focusing on business planning, product innovation, and marketing strategies, 30 teachers from 10 schools were trained. The program successfully improved participants' understanding of entrepreneurship concepts by 42%, as evidenced by pre-test and post-test comparisons. Participants developed 12 school-based business proposals utilizing local resources, including woven noken crafts, school agro-businesses, and digital education services. The Asset-Based Community Development (ABCD) approach proved effective in empowering teachers to identify and optimize existing school assets. Challenges such as limited capital and market access were addressed through crowdfunding training and partnerships with local cooperatives. The program not only enhanced teachers' entrepreneurial skills but also transformed their mindset from educators to change agents in school economic development. Recommendations include follow-up mentoring and curriculum integration to ensure sustainability.